Teachers’ Perspectives on the Issues and Challenges in the Implementation of Inclusive Education - Salguet, May Ann J. (Research and Advances in Education, 2025)
This qualitative study explored some issues and challenges encountered by MAPEH teachers in implementing inclusive education at Bagabag National High School, Nueva Vizcaya, Philippines. Using purposive sampling, nine teachers participated in semi-structured interviews. Thematic analysis generated three major themes: (1) selecting appropriate strategies and reinforcement, (2) recognizing diverse and individualized learning needs, and (3) viewing the teaching of learners with disabilities as a rewarding profession. Findings revealed that most teachers feel unprepared to teach learners with disabilities due to the absence of formal training, limited instructional materials, inadequate facilities, and insufficient stakeholder support. Despite these barriers, teachers demonstrated resilience by adapting strategies and fostering supportive learning environments. The study highlights the need for sustained professional development, improved resources, and policy-driven support to strengthen inclusive education practices. Recommendations include capacity-building programs, adequate funding, and strengthened collaboration among teachers, school leaders, and the Department of Education.